“Trait” and “state” aspects of fixation disparity during reading - Stephanie Jainta; Wolfgang Jaschinski (Journal of Eye Movement Research)
In our study, 14 subjects read 60 sentences from the Potsdam Sentence Corpus twice (viewing distance: 60 cm), while eye movements were measured with the EyeLink II. We analyzed fixation disparities for complete sentence replications (N=388). After subtracting the average fixation disparity of each sentence from each observation (which gave the “state” fixation disparity), 99% of all remaining fixation disparities were aligned, i.e. smaller than one character width (20 min arc) – depending mostly on incoming saccade amplitude and fixation position. Additionally, we measured the heterophoria for each subject during calibration and found a qualitative relationship between average, individual measures of fixation disparity (“trait” fixation disparity) and heterophoria, after dividing the sample in 3 groups of esophore, exophore and orthophore subjects. We showed that the magnitude of “trait” fixation disparity was biased by the direction of heterophoria: the more eso the heterophoria, the more eso the average sentence fixation disparity. In sum, despite a large “trait” fixation disparity (in the range of -6.6 to +33.6 min arc), “state” fixation disparities within a sentence were on average -0.9 (± 8.7) min arc and, thus, as precise as needed, i.e. within the expected extent of Panum’s area.